2014
DOI: 10.4028/www.scientific.net/kem.622-623.279
|View full text |Cite
|
Sign up to set email alerts
|

Formability Improvement Technique for Heated Sheet Metal Forming by Partial Cooling

Abstract: A forming process for heated sheet metal, such as hot-stamping, has limited use in deformable shapes. Higher temperature areas which have not yet come into contact with dies are more easily deformed; therefore, local deformation occurs at these areas which leads to breakage. To improve the formability of heated sheet metal, a deformation control technique utilizing the temperature dependence of flow stress is proposed. This technique can suppress local deformation by partial cooling around potential cracking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Beside this, the die temperature gradually increases during the production of parts quenched from high temperature, leading to severe wear that reduces the lifetime of the dies [70,71]. To overcome this limitation, as shown in Figure 6, Balint et al [72] and Ota et al [73] have proposed a novel process whereby the austenitised steel blanks are pre-cooled to a temperature just above the martensite start temperature before stamping. At this lower forming temperature, strain hardening can be enhanced, improving the drawability and formability; the productivity can also be increased by shortening the cooling cycle time.…”
Section: Low-temperature Hot Stampingmentioning
confidence: 99%
“…Beside this, the die temperature gradually increases during the production of parts quenched from high temperature, leading to severe wear that reduces the lifetime of the dies [70,71]. To overcome this limitation, as shown in Figure 6, Balint et al [72] and Ota et al [73] have proposed a novel process whereby the austenitised steel blanks are pre-cooled to a temperature just above the martensite start temperature before stamping. At this lower forming temperature, strain hardening can be enhanced, improving the drawability and formability; the productivity can also be increased by shortening the cooling cycle time.…”
Section: Low-temperature Hot Stampingmentioning
confidence: 99%
“…It is reported that cylindrical hole expansion by hot stamping prevent the cooling of the hole edge and increases the forming height. 11) As a method for improving the deep drawability of hot-stamped parts, Ota et al 12) proposed a method whereby air is injected onto the vulnerable upper wall of the step-shaped wall in the part being formed in order to increase the fracture strength of the part in contact with the punch shoulder. Also, reports have been published about technologies for preventing the temperature drop of the flange of the part by providing a gap between the die and the holder.…”
Section: Introductionmentioning
confidence: 99%
“…Nürnberger et al [20] studied the hot stamping of heat treatable steel 22MnB5 using water-air spray cooling. Ota et al [21] improved the formability by partial air cooling of potential cracking regions of blank to harden them before forming. Zhao et al [22] showed high hardness and minimum springback of a hot-stamped part by using rapid cooling to a forming temperature between 700 and 750 • C after ejecting from the furnace.…”
Section: Introductionmentioning
confidence: 99%